Distortion Compensation of Reconstructed Hologram Image in Digital Holographic Display Based on Viewing Window - Park, Minsik; Kim, Hyun‐Eui; Choo, Hyon‐Gon; Kim, Jinwoong; Park, Cheong Hee (ETRI journal, 2017)
A holographic display based on a viewing window enables the converging of a reconstruction wave into a viewing window by means of an optical system. Accordingly, a user can observe a reconstructed hologram image, even with a small diffraction angle. It is very difficult to manufacture an optical system with no aberrations; thus, it is inevitable that a certain amount of wave aberrations will exist. A viewing‐window‐based holographic display, therefore, always includes distortions in an image reconstructed from a hologram pattern. Compensating the distortions of a reconstructed image is a very important technical issue because it can dramatically improve the performance when reconstructing a digital three‐dimensional content image from a hologram pattern. We therefore propose a method for suppressing image distortion by measuring and compensating the wave aberration calculated from a Zernike polynomial, which can represent arbitrary wave aberrations. Through our experimental configuration using only numerical calculations, our proposed method decreased the reconstructed image distortion by more than 28%.